PENGARUH KUALITAS PRODUK DAN STORE ATMOSPHERE TERHADAP MINAT BELI ULANG (STUDI PADA NAKULA COFFEE CIKARANG) - Fadhila Hana Martaputri; Tetty Herawaty; Dian Fordian (JURNAL LENTERA BISNIS, 2025)
This study aims to determine the influence of product quality and store atmosphere on repurchase intention at Nakula Coffee Cikarang. The research method used is quantitative. Primary data was obtained through questionnaire distribution and unstructured interviews, while secondary data was collected through literature studies. The population in this study consists of Nakula Coffee customers. The sampling technique used in this research is purposive sampling. The research sample consists of 112 respondents who have consumed Nakula Coffee products on-site or dined in at least once. The data analysis technique used is multiple linear regression analysis. The results of this study indicate a positive influence of product quality on repurchase intention. Additionally, store atmosphere also has a positive influence on repurchase intention. Furthermore, product quality and store atmosphere together influence repurchase intention at Nakula Coffee.